AB0598 Nano-formulated lower dose nsaids preferred by patients experiencing acute pain. (23rd January 2014) - Strand, V.; Altman, R.; Daniels, S.; Manvelian, G.
Abstract : Background: NSAIDs are commonly prescribed for the relief of arthritic, musculoskeletal, and postoperative pain, yet safety and tolerability concerns still exist. We have completed 3 Phase 2 clinical trials in validated acute pain models to assess the analgesic efficacy and safety of the following investigational, nano-formulated, lower dose oral NSAIDs: diclofenac, indomethacin, and naproxen. Objectives: Determine patient's global evaluation of nano-formulated lower dose NSAIDs compared with placebo in an acute pain model. Methods: All 3 Phase 2 trials were multi-center, randomized, double-blind, single-dose, parallel-group, active- and placebo-controlled studies. Subjects were 18-50 years of age, had extraction of ≥2 third molars, and experienced moderate to severe pain intensity ≤6 h after surgery. Subjects received nano-formulated diclofenac, indomethacin, or naproxen, an active comparator (parent compound or celecoxib), or placebo. For global evaluation of study drug, subjects were asked "How effective do you think the study drug is as a treatment for pain?" Response choices were: 0=poor, 1=fair, 2=good, 3=very good, or 4=excellent. Subjects completed the evaluation 8h (nano-formulated indomethacin) or 12h (nano-formulated diclofenac and naproxen) after Time 0 or immediately before the first dose of rescue medication (whichever occurred first). The primary efficacy endpoints were sum of total pain relief (TOTPAR) 12 (diclofenac and naproxen) and TOTPAR-8 (indomethacin). Results: According to patient's global evaluation, there were statistically significant differences ( P <0.001) in patients evaluating the nano-formulated, lower dose NSAIDs as "very good" to "excellent" compared with placebo: 44.9% (22/49, nano-formulated diclofenac 18mg), 56.9% (29/51, nano-formulated diclofenac 35mg), 47.1% (24/51, celecoxib 400mg), and 9.8% (5/51, placebo); 18.0% (9/50, nano-formulated indomethacin 20mg), 56.9% (29/51, nano-formulated indomethacin 40mg), 51.0% (26/51, celecoxib 400mg), and 0.0% (0/51, placebo); 60.0% (30/50, nano-formulated naproxen 200mg), 72.5% (37/51, nano-formulated naproxen 400mg), 62.0% (31/50, naproxen 250mg), 74.5% (38/51, naproxen 500mg), and 13.7% (7/51, placebo). Numerical values were similar for nano-formulated naproxen and corresponding higher dose of standard naproxen, and nano-formulated diclofenac and indomethacin and the loading dose of celecoxib. The nano-formulated NSAIDs exhibited statistically significant improvements ( P <0.001) in TOTPAR-8 or -12 compared with placebo. There were no differences in safety and tolerability data between treatment groups and placebo. Conclusions: The use of investigational, nano-formulated, lower dose oral NSAIDs was favored over placebo and demonstrated good efficacy in an acute pain model. These Phase 2 data indicate that nano-formulated, lower doses of diclofenac, indomethacin, and naproxen provide pain relief at a lower dose and deserve further investigation in Phase 3 clinical trials. These products may provide therapeutic options in accordance with the FDA directive to use the lowest effective NSAID dose. Disclosure of Interest: V. Strand Consultant for: Participant at advisory board for Iroko Pharmaceuticals, R. Altman Consultant for: Participant at advisory board for Iroko Pharmaceuticals, S. Daniels Consultant for: Employee of Premier Research Group International, LLC, which was contracted to complete this Phase 2 clinical trial, G. Manvelian Consultant for: Medical consultant to Iroko Pharmaceuticals